Pengaruh Financial Technology dan Lingkungan Sosial Terhadap Perilaku Pengelolaan Keuangan Mahasiswa dengan Locus of control Sebagai Moderasi (Studi Kasus Pada Mahasiswa Universitas Slamet Riyadi Surakarta) - Dyah Ayu Ratri Pramesti; Bambang Widarno (ProBank, 2025)
This research seeks to analyze the impact of financial technology and the social environment on students' financial management behavior, with locus of control serving as a moderating variable. The study employs a quantitative approach, utilizing primary data as its source. The population targeted consists of students from Slamet Riyadi University Surakarta, with a total sample of 378 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression and moderated regression analysis (MRA). The findings reveal that both financial technology and the social environment have a significant positive influence on students' financial management behavior. However, locus of control does not significantly moderate this relationship. This suggests that while locus of control may theoretically affect personal financial management, its moderating effect on the influence of financial technology and the social environment is limited. Therefore, it is essential to enhance individual awareness and responsibility in managing financial behavior, as well as to promote education on the effective use of financial technology and the role of the social environment in fostering independent and responsible financial decision-making.